KARAKTERISTIK SOSIAL BUDAYA NELAYAN DAN AKSES INFORMASI DI KECAMATAN PULAU BUNYU KABUPATEN BULUNGAN KALIMANTAN UTARA - Azman Saputra; Juliani; Zul Asman Randika (Jurnal Pembangunan Perikanan dan Agribisnis, 2015)
The aims of this research was to determine the characteristics social culture of fisherman and what type of information access commonly used by fishing communities located on the Bunyu Island of Bulungan Regency North Kalimantan. This research was conducted for 8 (eight) months with research sites on the Bunyu Island District Of Bulungan Regency North Kalimantan. Data collection conducted a survey, which is the object of research and observation to conduct structured interviews with respondents. The data required in this research include primary data and secondary data. The results of this research indicated that in local belief Bunyu Island Community there are some matter is to attention fisherman which what to do and not to do, there is the prohibition for fisherman before and will going to the ocean. The information access through interpersonal media through extension agents. Most respondents are more up to date on the fishing of fisheries officers and information supporting information and access to information through fellow fishermen say they are interconnected and share information with one another. While access to information through peer group Evidently many benefits perceived by respondents in each group as a forum to tighten silaturahmi among members through regular meetings are held.